2009
DOI: 10.1007/s11064-009-0006-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Attenuates Neuronal Injury Induced by Vascular Dementia Via Inhibiting Apoptosis in Rats

Abstract: Hydrogen sulfide (H(2)S) is a gaseous messenger and serves as an important neuromodulator in the central nervous system. The current study was undertaken to investigate whether H(2)S attenuates the neuronal injury induced by vascular dementia (VD). Rats were subjected to bilateral common carotid artery and vertebral artery occlusion for 5 min three times in an interval of 5 min to induce VD. An H(2)S donor, sodium hydrosulfide (NaHS) or an inhibitor of cystathionine-beta-synthase, hydroxylamine (HA) was admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 55 publications
(66 reference statements)
8
43
0
1
Order By: Relevance
“…This may be attributable to the hypothesis that a lower concentration of H 2 S exerts a protective effect on cells while higher levels of H 2 S exposure lead to cytotoxicity (41). In the present study, 14 µmol/kg/day NaHS was intraperitoneally administered, and it has previously been confirmed that the protective effect against neuronal injury conferred by NaHS is dose-dependent (42). In addition to its function as an inhibitor of CBS, hydroxylamine can be metabolized to NO (43), which may be neurotoxic and contributes to neuronal damage (44).…”
Section: A B C Dsupporting
confidence: 61%
“…This may be attributable to the hypothesis that a lower concentration of H 2 S exerts a protective effect on cells while higher levels of H 2 S exposure lead to cytotoxicity (41). In the present study, 14 µmol/kg/day NaHS was intraperitoneally administered, and it has previously been confirmed that the protective effect against neuronal injury conferred by NaHS is dose-dependent (42). In addition to its function as an inhibitor of CBS, hydroxylamine can be metabolized to NO (43), which may be neurotoxic and contributes to neuronal damage (44).…”
Section: A B C Dsupporting
confidence: 61%
“…Niu and colleagues reported that neutralization of FasL attenuates brain inflammation in a model of experimental stroke in mice [41] . The anti-apoptotic effects of H 2 S have been widely reported by researchers both in vivo and in vitro [42][43][44] . However, few studies have investigated the effects of H 2 S on HS, and even fewer have addressed the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The antiapoptotic effect was supported by other studies as well. Zhang et al found out that H 2 S attenuated neuronal injury induced by vascular dementia via inhibiting apoptosis in rats (Zhang et al 2009). In yet another study, H 2 S imparted the cytoprotective effect to PC12 cells against amyloid β (25-35)-induced apoptosis (Tang et al 2008).…”
Section: Anti-apoptosismentioning
confidence: 99%